Electroplated titanium anode for PCB (Printed Circuit Board) and preparation method of electroplated titanium anode

By adding sodium dodecyl sulfonate to the surface barrier layer of the PCB titanium anode, a stable three-dimensional porous morphology is formed, which solves the problem that the barrier layer cannot fully cover the catalytic layer, reduces the oxygen evolution potential and additive consumption, and improves the uniformity and aging life of the plating.

CN119710883APending Publication Date: 2025-03-28JIANGXI STANDE ELECTRODE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411885419.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when preparing PCB titanium anode, the barrier layer cannot fully cover the catalytic layer, resulting in an increase in the oxygen evolution potential of the anode, increasing the consumption and energy consumption of additives.

Method used

An electroplated titanium anode for PCB is adopted, which includes a matrix bonding layer, an intermediate active layer and a surface barrier layer. By adding sodium dodecyl sulfonate to the coating liquid of the surface barrier layer, a stable three-dimensional porous morphology is formed to ensure that the barrier layer completely covers the catalytic layer.

Benefits of technology

Complete coverage of the barrier layer is achieved, the oxygen evolution potential is reduced, the consumption and energy consumption of additives are reduced, and the uniformity and aging life of the coating are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710883A_ABST
    Figure CN119710883A_ABST
Patent Text Reader

Abstract

The invention discloses an electroplated titanium anode for a PCB (printed circuit board) and a preparation method thereof, and belongs to the technical field of electrocatalysis, the electroplated titanium anode comprises a matrix binding layer, a middle active layer and a surface barrier layer which are sequentially arranged on a substrate, the matrix binding layer is mainly made of oxides of Ti and Ta, the middle active layer is mainly made of oxides of Ta and Ir, and the surface barrier layer is mainly made of oxides of Ta and Ir. The surface barrier layer is mainly made of valve metal oxide, sodium dodecyl sulfate is added into coating liquid of the surface barrier layer, and the preparation method comprises the step of sequentially coating and sintering the matrix bonding layer, the middle active layer and the surface barrier layer on the base material. According to the invention, the coating preparation of the anode plate is carried out through proper coating liquid formula, coating liquid dosage, coating times, sintering time and the like, and a stable three-dimensional porous morphology with a proper pore diameter is simply and efficiently formed on the PCB anode, so that the barrier layer completely covers the catalyst layer, and the barrier layer does not increase the oxygen evolution potential of the anode, and the performance of the anode is improved. And the consumption of the additive can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention mainly relates to the field of electrocatalysis technology, and specifically relates to an electroplated titanium anode for PCB and a preparation method thereof. Background Art

[0002] With the continuous development of electronic technology, the performance requirements for printed circuit boards (PCBs) are getting higher and higher, especially in the fields of high-density interconnection and micro-hole electroplating. In order to meet these needs, researchers began to explore PCB anodes with special morphologies. Among them, anodes with three-dimensional porous morphology can significantly improve electroplating efficiency, improve coating quality, and reduce energy consumption due to their large surface area, good conductivity and electrolyte permeability.

[0003] At present, the methods for forming three-dimensional porous morphology mainly include chemical corrosion, electrochemical corrosion, template method, etc. Chemical corrosion usually requires the use of corrosive reagents such as strong acids and alkalis, which is not only dangerous to operate, but also unfriendly to the environment. Although the electrochemical corrosion method can control the formation of porous morphology to a certain extent, the process parameters are relatively complex and require precise control of parameters such as current density, voltage, and time, otherwise it is easy to cause uneven porous morphology. The template method requires the use of specific template materials, the preparation process is cumbersome, and the cost is high. It can be seen that these methods obviously have many factors that are difficult to operate when preparing titanium anodes.

[0004] Because the three-dimensional porous morphology has pores that allow electrolyte penetration, it can maintain stability and withstand the volume changes that occur during redox reactions. Despite their structural challenges, incorporating 3D nanoporous structures into these electrodes can ease ion transport by shortening the ion diffusion path length and minimizing the resistance at the electrode / electrolyte interface due to their increased pore volume, exposing more electrochemically active sites.

[0005] After coating the active catalytic layer in the PCB titanium anode coating process, the barrier coating solution is then coated. In theory, the dense surface barrier layer can block the oxygen free radicals formed by the catalytic layer from penetrating and oxidizing the additives in the solution. However, the barrier layer in the prior art cannot completely cover the catalytic layer, and the barrier layer will increase the oxygen evolution potential of the anode to a certain extent, which will lead to a large consumption of additives and high energy consumption at the anode. It is necessary to improve the anode preparation method so that it does not increase the oxygen evolution potential while completely covering the catalytic layer, and reduce the oxidation consumption of the anode on the additive. Therefore, there is an urgent need for a new preparation method that can simply and efficiently form a stable three-dimensional porous morphology with a suitable pore size on the PCB anode. Summary of the invention

[0006] The technical solution of the present invention aims at the technical problem that the existing technical solution is too single, and provides a solution that is significantly different from the existing technology. It mainly provides a titanium electroplating anode for PCB and a preparation method thereof, which is used to simply and efficiently form a stable three-dimensional porous morphology with suitable pore size on the PCB anode.

[0007] The technical solution adopted by the present invention to solve the above technical problems is: A titanium electroplating anode for PCB comprises a substrate bonding layer, an intermediate active layer and a surface barrier layer which are sequentially arranged on a substrate, wherein the material of the substrate bonding layer is mainly Ti and Ta oxides, the material of the intermediate active layer is mainly Ta and Ir oxides, the material of the surface barrier layer is mainly valve metal oxides, and sodium dodecyl sulfate is added to the coating liquid of the surface barrier layer.

[0008] Furthermore, the solubility of sodium dodecyl sulfate in the coating solution of the surface barrier layer is 1.000-2.000 g / L.

[0009] Furthermore, the valve metal in the surface barrier layer is at least one of Ta, Nb, Zr, V, and Sn; And / or, the mass ratio per unit area of ​​Ir in the intermediate active layer to the valve metal in the surface barrier layer is 5-15:2-6.

[0010] The present invention also discloses a method for preparing an electroplated titanium anode for PCB, which is used to prepare the electroplated titanium anode for PCB; the method comprises the following steps: S1, cutting, removing impurities, cleaning and drying the titanium mesh to obtain a substrate; S2, first coating the substrate obtained after treatment in S1 with a substrate bonding layer coating liquid, then sintering at 500-550°C for 15-30 min, and finally cooling to room temperature; repeating this step 2-6 times; S3, first apply the intermediate active layer coating liquid on the substrate bonding layer, then sinter at 500-550°C for 15-30 minutes, and finally cool to room temperature; repeat this step 3-5 times; S4. First, take the valve metal solution, add sodium dodecyl sulfate to prepare a surface barrier coating solution, the solubility of sodium dodecyl sulfate in the coating solution is 1.000-2.000 g / L; then apply the surface barrier coating solution on the intermediate active layer, and then sinter at 500-550 ° C for 15-30 min, and finally cool to room temperature; repeat this step 1-6 times.

[0011] Furthermore, in step S1, the cut substrate is immersed in 10 to 30 wt % hydrochloric acid for 10 to 30 min.

[0012] Furthermore, in step S2, the substrate bonding layer coating liquid mainly comprises TiCl4 and TaCl5, and the mass ratio of the two is 1-3:4-6.

[0013] Furthermore, in step S2, 0.20 to 0.40 g of the substrate bonding layer coating solution is weighed each time, and Ti and Ta are increased by 0.6 to 1.2 g / m after each coating. 2 .

[0014] Furthermore, in step S3, the intermediate active layer coating liquid mainly comprises H2IrCl6▪6H2O and TaCl5, and the mass ratio of the two is 5-9:1-3.

[0015] Furthermore, in step S3, 0.25 to 0.50 g of the intermediate active layer coating solution is weighed each time, and Ta and Ir are increased by 1.0 to 2.0 g / m after each coating. 2 .

[0016] Further, in step S4, 0.15 to 0.50 g of the surface barrier coating solution is weighed each time, and the valve metal element increases by 0.5 to 1.5 g / m after each coating. 2 .

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The material of the barrier layer in the present invention is mainly valve metal oxide, and sodium dodecyl sulfonate is added to the coating liquid of the surface barrier layer. The solubility of sodium dodecyl sulfonate in the coating liquid of the surface barrier layer is also limited. From the perspective of material design, the barrier layer of the present invention is based on the fine regulation of the surface and interface properties of the material. The design of the existing anode barrier layer mainly focuses on the barrier performance of the material itself, and less consideration is given to improving its microstructure and interface properties by adding small molecule surfactants. Based on the fact that the barrier layer uses valve metal oxide, sodium dodecyl sulfonate is selected as an additive. The chemical stability of the valve metal oxide will not be affected, and the structure and performance of the barrier layer will not be damaged. As an additive, sodium dodecyl sulfonate participates in the formation process of the barrier layer and changes the growth mechanism of the barrier layer. During the preparation process, it will affect the crystallization process of the barrier layer material, make the crystal growth more orderly, reduce grain boundary defects, and promote the formation of a three-dimensional porous morphology on the anode surface. Compared with the chemical corrosion method, electrochemical corrosion method, and template method in the prior art, the method of the present invention has higher operation safety and is environmentally friendly; the process parameters are relatively simple; the preparation process is simple and the cost is low, that is, the present invention can simply and efficiently form a stable three-dimensional porous morphology on the PCB anode.

[0018] (2) The present invention coats the anode plate through appropriate coating liquid formula, coating liquid dosage, coating times and sintering time, forming a three-dimensional porous morphology with appropriate pore size, the pore size range of which satisfies the requirement of being larger than the diameter of water molecules and smaller than the molecular diameter of each additive in the electrolyte; it reduces the surface tension of the solution so that the barrier layer completely covers the catalytic layer; and the appropriate pore size causes the barrier layer to prevent the additive molecules in the electrolyte from contacting the anode active sites, and water molecules can easily pass through, without affecting the electrocatalytic process of electrolyzing water, thereby not causing the oxygen evolution potential to increase; within the same electroplating time, the anode of the present invention can make the metal plating in the blind hole of the PCB thicker and more uniform, and the barrier layer completely covers the catalytic layer, which helps to distribute the current more evenly on the anode surface, reduce the current concentration and local overheating, improve the aging life, and reduce the consumption of additives. This is very important for the electroplating of complex circuits on PCBs, and can avoid problems such as inconsistent plating thickness and reduced plating quality caused by uneven current, and reduce the cost of additives.

[0019] (3) The titanium substrate bonding layer in the present invention is mainly composed of Ti and Ta oxides, which prevents the passivation of titanium by forming a dense metal oxide layer on the titanium surface, thereby greatly improving the service life of the anode, effectively preventing oxygen molecules and atoms from diffusing into the substrate, and improving the bonding strength between the substrate and the coating.

[0020] (4) In the present invention, the intermediate active layer is an oxide of Ta and Ir. Ta is added to both the intermediate active layer and the titanium substrate bonding layer, which can reduce the thermal stress generated by the mismatch of thermal expansion coefficients between the titanium substrate bonding layer and the intermediate active layer, and is beneficial to preventing cracks and falling off of the intermediate active layer. Ir is an active substance for OER (oxygen evolution reaction), reflecting the main function of the active layer.

[0021] (5) The surface barrier layer in the present invention is a valve metal (Ta, Nb, Zr, V, Sn, etc.) oxide, which can effectively prevent the diffusion of oxygen molecules and atoms. By adding an appropriate amount of sodium dodecyl sulfate, the surface barrier layer is completely covered on the intermediate active layer, which can prevent the additive molecules from contacting and being oxidized when oxygen free radicals are generated in the intermediate active layer of the anode.

[0022] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM images of the surface of the titanium anode coating prepared in Example 1, wherein (a), (b), and (c) are of 10 μm, 3 μm, and 1 μm specifications, respectively; Figure 2The SEM images of the titanium anode coating surface prepared in Comparative Example 1, wherein (a), (b), and (c) are of 10 μm, 3 μm, and 1 μm specifications, respectively; Figure 3 The diagram is an indication of the edge and middle positions of the titanium anode grid structure prepared in Example 1, wherein A represents the edge of the grid and B represents the middle of the grid; Figure 4 The cross section of the titanium anode coating prepared in Example 1; Figure 5 Flow chart of the method for preparing the electroplated titanium anode for PCB in the embodiment; Figure 6 The linear scanning voltammetry data diagram of the titanium anode prepared in Example 1 and Comparative Example 1, the abscissa is the electrode potential compared to the saturated calomel electrode, and the ordinate is the current density. DETAILED DESCRIPTION

[0024] To facilitate understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings, but the present invention can be implemented in different forms and is not limited to the embodiments described in the text. On the contrary, these embodiments are provided to make the content disclosed in the present invention more thorough and comprehensive.

[0025] Embodiment 1: A method for preparing a titanium electroplating anode for PCB, comprising the following steps: a. Cut a titanium mesh of 10 cm x 10 cm and soak it in 30wt% hydrochloric acid for 30 min to remove oil and oxide layer, then wash it with distilled water and dry it; b. Take 0.20g of a mixture of TiCl4 and TaCl5 (the mass ratio of the two is 3:4) as the substrate bonding layer coating liquid, apply the substrate bonding layer coating liquid on the titanium mesh treated in step a, then sinter at 520℃ for 15 min, and finally cool to room temperature; repeat the coating and sintering steps 3 times, and the weight of Ti and Ta increases by about 0.6g / m each time. 2 ; c. Take 0.27g of H2IrCl6▪6H2O and TaCl5 mixed solution (the mass ratio of the two is 9:1) as the intermediate active layer coating solution, evenly coat it on the substrate bonding layer in step b, sinter at 520℃ for 30min and then cool to room temperature. Repeat the coating and sintering steps 5 times. The weight of Ir and Ta increases by about 1.1g / m each time. 2 ; d. Weigh 0.075 g of sodium dodecyl sulfate, take an appropriate amount of TaCl5 solution to dissolve it and pour it into a 50 mL volumetric flask, then take TaCl5 solution to make it 50 mL to prepare a surface barrier coating solution, the solubility of sodium dodecyl sulfate in the coating solution is 1.500 g / L; take 0.27 g of the surface barrier coating solution and evenly coat it on the intermediate active layer in step c, sinter it at 520 ° C for 15 min and then cool it to room temperature, repeat the coating and sintering steps 6 times, and obtain a surface barrier layer with a Ta content of 5 g / m 2 (Ta gains weight by about 0.83g / m each time 2 ) PCB with electroplated titanium anode.

[0026] In this embodiment, the mass ratio per unit area of ​​Ir in the intermediate active layer and Ta in the surface barrier layer is 5.5:5.

[0027] Embodiment 2: This embodiment differs from Embodiment 1 in that: In step a, soak in 20wt% hydrochloric acid for 10 minutes.

[0028] In step b, 0.3 g of a mixture of TiCl4 and TaCl5 (the mass ratio of the two is 1:2) is taken; sintered at 500°C for 30 min; the coating and sintering steps are repeated 6 times, and the weight of Ti and Ta increases by about 0.9 g / m each time. 2 .

[0029] In step c, 0.50 g of a mixture of H2IrCl6▪6H2O and TaCl5 (the mass ratio of the two is 7:2) is taken as the intermediate active layer coating solution; sintered at 500 °C for 25 min and then cooled to room temperature, and the coating and sintering steps are repeated 3 times, and the weight of Ir and Ta increases by about 2.0 g / m each time. 2 .

[0030] In step d, NbCl5 solution was used instead of TaCl5 solution, and 0.15 g of surface barrier coating solution was taken; after sintering at 500 °C for 30 min; the coating and sintering steps were repeated 4 times, and the Nb content in the surface barrier layer was 2 g / m 2 (Nb increases by about 0.5 g / m each time 2 ).

[0031] In this embodiment, the mass ratio per unit area of ​​Ir in the intermediate active layer and Nb in the surface barrier layer is 4.5:2.

[0032] The rest is the same as the first embodiment.

[0033] Embodiment 3: This embodiment differs from Embodiment 1 in that: In step a, soak in 10wt% hydrochloric acid for 20 minutes.

[0034] In step b, 0.40 g of a mixture of TiCl4 and TaCl5 (the mass ratio of the two is 1:6) is taken; sintered at 550°C for 15 min; the coating and sintering steps are repeated twice, and the weight of Ti and Ta increases by about 1.2 g / m each time. 2 .

[0035] In step c, 0.40 g of a mixture of H2IrCl6▪6H2O and TaCl5 (the mass ratio of the two is 5:3) is taken as the intermediate active layer coating solution, sintered at 550 °C for 10 min and then cooled to room temperature. The coating and sintering steps are repeated 4 times, and the weight of Ir and Ta increases by about 1.6 g / m each time. 2 .

[0036] In step d, ZrCl3 solution was used instead of TaCl5 solution, and 0.50 g of surface barrier coating solution was taken; after sintering at 550 °C for 15 min; the coating and sintering steps were repeated once, and the Zr content in the surface barrier layer was 1.5 g / m 2 .

[0037] In this embodiment, the mass ratio per unit area of ​​Ir in the intermediate active layer and Zr in the surface barrier layer is 4:1.5.

[0038] The rest is the same as the first embodiment.

[0039] Embodiment 4: This embodiment differs from Embodiment 1 in that: In step c, 0.25 g of H2IrCl6▪6H2O and TaCl5 mixed solution (the mass ratio of the two is 5:3) is taken, and the coating and sintering steps are repeated 5 times, and the weight of Ir and Ta increases by about 1.0 g / m each time. 2 ; In step d, VCl2 solution is used instead of TaCl5 solution, 0.05 g of sodium dodecyl sulfate is weighed, and the solubility of sodium dodecyl sulfate in the coating solution is 1.000 g / L; 0.3 g of the surface barrier coating solution is taken; the coating and sintering steps are repeated 6 times to obtain a V content of 6 g / m in the surface barrier layer. 2 (V each weight gain is about 1 g / m 2 ) PCB with electroplated titanium anode.

[0040] In this embodiment, the mass ratio per unit area of ​​Ir in the intermediate active layer and V in the surface barrier layer is 5:6.

[0041] The rest is the same as the first embodiment.

[0042] Embodiment 5: This embodiment differs from Embodiment 1 in that: In step c, 0.38 g of H2IrCl6▪6H2O and TaCl5 mixed solution (the mass ratio of the two is 5:3) is taken, and the coating and sintering steps are repeated 5 times, and the weight of Ir and Ta increases by about 1.5 g / m each time. 2 ; In step d, SnCl2 solution is used instead of TaCl5 solution, 0.10 g of sodium dodecyl sulfate is weighed, and the solubility of sodium dodecyl sulfate in the coating solution is 2.000 g / L; 0.4 g of the surface barrier coating solution is taken; the coating and sintering steps are repeated once to obtain a surface barrier layer with a Sn content of 1 g / m 2 The PCB is electroplated with titanium anode.

[0043] In this embodiment, the mass ratio per unit area of ​​Ir in the intermediate active layer and Sn in the surface barrier layer is 7.5:1.

[0044] The rest is the same as the first embodiment.

[0045] Comparative Example 1: The preparation steps are basically the same as those in Example 1, except that sodium dodecyl sulfate is not added to the surface barrier layer coating solution in step d.

[0046] Comparative Example 2: The preparation steps are basically the same as those in Example 1, except that in step d, the solubility of sodium dodecyl sulfate in the surface barrier layer coating solution is 0.500 g / L.

[0047] The SEM images of the coating surfaces of the electroplated titanium anode samples for PCB prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 and Figure 2 shown.

[0048] contrast Figure 1 and Figure 2 It can be seen that the titanium anode coating prepared in Example 1 grows a more obvious three-dimensional porous structure, indicating that the addition of sodium dodecyl sulfate can promote the formation of a three-dimensional porous structure.

[0049] The contents of Ir and Ta in the middle and edge of the grid of the electroplated titanium anode samples for PCB prepared in Example 1, Comparative Example 1 and Comparative Example 2 were detected. The positions of the grid edge and the middle are as follows: Figure 3 As shown, the Ir and Ta contents at these two locations are shown in Table 1: Table 1 Ir and Ta content in the middle and edge of titanium grid

[0050] It can be seen from Table 1 that the presence of Ir cannot be detected in the middle and edge of the grid of the titanium anode in Example 1; while the presence of Ir cannot be detected in the middle of Comparative Example 1, but more Ir can be detected in the edge; the presence of Ir cannot be detected in the middle of Comparative Example 2, but a small amount of Ir can be detected in the edge. This indicates that by adding an appropriate amount of sodium dodecyl sulfate, the barrier layer can completely cover the catalytic layer. When the appropriate concentration is not reached, the thickness of the barrier layer at the edge may be insufficient, and the EDS sampling depth is just reached, resulting in the detection of a small amount of Ir.

[0051] The FIB (focused ion beam microscopy) characterization of the titanium anode in Example 1 is as follows: Figure 4 As shown, the thicknesses of the titanium substrate bonding layer, the intermediate active layer and the surface barrier layer are 235.40 nm, 1.138 μm and 1.398 μm respectively, and the thickness of each coating is uniform, and the surface barrier layer covers the intermediate active layer tightly.

[0052] The titanium electroplating anode samples for PCB prepared in Example 1 and Comparative Example 1 were subjected to accelerated life test, additive consumption test and oxygen evolution potential test respectively, and the specific steps are as follows: (1) Accelerated aging life test The PCB cut into 2 cm x 2 cm was electroplated with a titanium anode sample as the anode, and another titanium plate was used as the cathode. The electrolyte was a 20% mass fraction H2SO4 solution. A DC power supply was used for electrolysis, and the current density was set to 25 KA / m 2 When the voltage rises by 5 V compared to the initial voltage, the anode fails and the accumulated electrolysis time is recorded.

[0053] (2) Additive consumption test A PCB cut into 2 cm x 2 cm was used as the anode using the electroplated titanium anode sample. A 1 mm thick titanium plate was used as the cathode. The cathode area was 2 cm x 5 cm. The electrolyte was a copper sulfate solution with a copper sulfate concentration of 200 g / L, a sulfuric acid concentration of 40 g / L, and a chloride ion concentration of 40 mg / L. A leveling agent of 1 mg / L, a brightener of 10 mg / L, and an inhibitor of 11 mg / L were added to the electrolyte. A DC power supply was used for electrolysis for 6 h, and the current density was set to 250 A / m 2 . Use CVS to test the changes in the additive content in the electrolyte before and after electrolysis.

[0054] The results of the accelerated aging life test and additive consumption test are shown in Table 2 below: Table 2 Accelerated life test and additive consumption test data

[0055] It can be seen from Table 2 that, compared with Comparative Example 1, by adding sodium dodecyl sulfate to the surface barrier layer coating solution in Example 1, the aging life can be significantly extended, and the consumption of additives such as leveling agents, brighteners, and inhibitors is also greatly reduced; compared with Comparative Example 2, by controlling the appropriate addition amount of sodium dodecyl sulfate in Example 1, the aging life can be significantly extended, and the consumption of additives such as leveling agents, brighteners, and inhibitors is further reduced.

[0056] (3) Oxygen evolution potential test By linear sweep voltammetry test, the titanium anodes in Example 1 and Comparative Example 1 were used as working electrodes, respectively, with an area of ​​2 cm x 2 cm, a Pt mesh electrode as the counter electrode, and a calomel electrode as the reference electrode; the electrolyte was 100 mL of 0.5 mol / L H2SO4 solution, and the test results were as follows: Figure 6 As shown. It can be found that as the voltage increases, the current density of the titanium anode with three-dimensional porous morphology obtained in Example 1 becomes larger and larger than that of the current density of Comparative Example 1 at the same potential. This shows that the anode with three-dimensional porous morphology and suitable pore size has a lower oxygen evolution potential.

[0057] In summary, it can be seen that the surface barrier layer based on the valve metal oxide can promote the formation of a three-dimensional porous structure with a suitable pore size by adding an appropriate amount of sodium dodecyl sulfate, and the surface barrier layer still covers the intermediate active layer tightly, so the probability of the additive directly contacting the intermediate active layer is reduced, and the loss of active sites in the catalytic layer is lower. This is also the reason why it can improve the aging life and reduce the consumption of additives. In addition, the three-dimensional porous structure with a suitable pore size makes the current more dispersed, and there will be no more oxidizing active sites, which is also one of the reasons for reducing the consumption of additives.

[0058] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A titanium electroplating anode for PCB, characterized in that: It includes a substrate bonding layer, an intermediate active layer and a surface barrier layer which are sequentially arranged on a substrate. The material of the substrate bonding layer is mainly Ti and Ta oxides, the material of the intermediate active layer is mainly Ta and Ir oxides, the material of the surface barrier layer is mainly valve metal oxides, and sodium dodecyl sulfate is added to the coating liquid of the surface barrier layer.

2. The electroplated titanium anode for PCB according to claim 1, characterized in that: The solubility of sodium dodecyl sulfate in the coating solution of the surface barrier layer is 1.000-2.000 g / L.

3. The electroplated titanium anode for PCB according to claim 1, characterized in that: The valve metal in the surface barrier layer is at least one of Ta, Nb, Zr, V, and Sn; And / or, the mass ratio per unit area of ​​Ir in the intermediate active layer to the valve metal in the surface barrier layer is 5-15:2-6.

4. A method for preparing an electroplated titanium anode for PCB, used for preparing the electroplated titanium anode for PCB according to any one of claims 1 to 3; characterized in that: The steps include: S1, cutting, removing impurities, cleaning and drying the titanium mesh to obtain a substrate; S2, first coating the substrate obtained after treatment in S1 with a substrate bonding layer coating liquid, then sintering at 500-550°C for 15-30 min, and finally cooling to room temperature; repeating this step 2-6 times; S3, first apply the intermediate active layer coating liquid on the substrate bonding layer, then sinter at 500-550°C for 15-30 min, and finally cool to room temperature; repeat this step 3-5 times; S4. First, take the valve metal solution, add sodium dodecyl sulfate to prepare a surface barrier coating solution, the solubility of sodium dodecyl sulfate in the coating solution is 1.000-2.000 g / L; then apply the surface barrier coating solution on the intermediate active layer, and then sinter at 500-550 ° C for 15-30 min, and finally cool to room temperature; repeat this step 1-6 times.

5. The method for preparing a titanium electroplating anode for PCB according to claim 4, characterized in that: In step S1, the cut substrate is immersed in 10-30 wt % hydrochloric acid for 10-30 min.

6. The method for preparing a titanium electroplating anode for PCB according to claim 4, characterized in that: In step S2, the substrate bonding layer coating liquid mainly comprises TiCl4 and TaCl5, and the mass ratio of the two is 1-3:4-6.

7. The method for preparing a titanium electroplating anode for PCB according to claim 6, characterized in that: In step S2, 0.20-0.40 g of substrate bonding layer coating solution is weighed each time, and Ti and Ta are increased by 0.6-1.2 g / m after each coating. 2 .

8. The method for preparing a titanium electroplating anode for PCB according to claim 4, characterized in that: In step S3, the intermediate active layer coating liquid mainly comprises H2IrCl6▪6H2O and TaCl5, and the mass ratio of the two is 5-9:1-3.

9. The method for preparing a titanium electroplating anode for PCB according to claim 8, characterized in that: In step S3, 0.25-0.50 g of the intermediate active layer coating solution is weighed each time, and Ta and Ir are increased by 1.0-2.0 g / m after each coating. 2 .

10. The method for preparing a titanium electroplating anode for PCB according to claim 4, characterized in that: In step S4, 0.15 to 0.50 g of the surface barrier coating solution is weighed each time, and the valve metal element is increased by 0.5 to 1.5 g / m after each coating. 2 .